Financial Literacy and Entrepreneurial Finance In Bumdesa Management Study - Setyobakti, Moh. Hudi; Istifadah, Istifadah; Awwaliyah, Intan; Kasno, Kasno (Jurnal Ilmu Manajemen Advantage, 2021)
The purpose of this study is to get an overview of the knowledge and financial aspects of entrepreneurship to be a decisive part in the management of Bumdesa. The method used in this research is descriptive qualitative with a case study approach. The results obtained are from the aspect of financial literacy of the Bumdesa management on human resource input, knowledge of the preparation of financial reports and the inadequate ability to analyze financial statements so that they have not been able to make financial reports as a basis for decision making. The financial aspect of entrepreneurship can be seen from the Bumdesa business idea. running a business idea, the ability to organize a business, develop innovation as a whole have been implemented, but have not run optimally, so that it has an impact on the Bumdesa financial performance.